(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aimed to evaluate the reality of the work environment in Baniyas Refinery Company through its dimensions (organizational structure, training, incentives and rewards, technology, working conditions); The research adopted a comprehensive inventory method in distributing questionnaires to the 370 administrative workers in the Baniyas Refinery Company, according to statistics from the Administrative Development Directorate in the company under study. The available data was analyzed using appropriate statistical tests, such as the t-test for one sample and relying on the SPSS program. The results of the study indicated that the work environment in the company under study is acceptable and satisfactory, according to the opinions of the research sample. The research presented a set of recommendations, including: the necessity of continuing to improve the organizational structure in order to be compatible with the changes occurring in the surrounding environment, paying attention to training programs and that they be developed based on the departments’ need for training and the type of programs they need by submitting a proposal from the work heads to Its affiliated directorates, in addition to developing an incentive system that takes into account the need for the incentives granted to be commensurate with the standard of living, interest in technology, reliance on local expertise in modernizing the technology used, and improving the working conditions surrounding the worker, including lighting, ventilation, temperature, and work spaces, in a way that helps facilitate work. The work assigned to him and the provision of security and safety procedures at work by adhering to the established rules and laws.